Construction of self-supporting, hierarchically structured caterpillar-like NiCo2S4 arrays as an efficient trifunctional electrocatalyst for water and urea electrolysis. Issue 3 (15th January 2021) - Song, Wenjiao; Xu, Mingze; Teng, Xue; Niu, Yanli; Gong, Shuaiqi; Liu, Xuan; He, Xiaoming; Chen, Zuofeng
Abstract : In this study, self-supporting, hierarchically structured caterpillar-like NiCo2 S4 arrays are constructed as an efficient trifunctional electrocatalyst for water and urea electrolysis. Abstract : In this study, we have developed intriguing self-supporting caterpillar-like spinel NiCo2 S4 arrays with a hierarchical structure of nanowires on a nanosheet skeleton, which can be used as a self-supporting trifunctional electrocatalyst for the oxygen evolution reaction (OER), hydrogen evolution reaction (HER) and urea oxidation reaction (UOR). The caterpillar-like NiCo precursor arrays are first in situ grown on carbon cloth (NiCo2 O4 /CC) by a facile hydrothermal reaction, which is followed by an anion exchange process (or sulfuration treatment) with Na2 S to form self-supporting spinel NiCo2 S4 arrays (NiCo2 S4 /CC) with a roughened nanostructure. Taking advantage of the bimetallic synergistic effect, the unique hierarchical nanostructure, and the self-supporting nature, the resultant NiCo2 S4 /CC electrode exhibits high activities toward the OER, HER and UOR, which are highly superior to the monometallic counterparts of NiS nanosheets and Co9 S8 nanowires on a carbon cloth substrate. The comparison of the three electrodes also indicates that the hierarchically structured bimetallic electrode combines the morphological and structural characteristics of monometallic Ni-based nanosheets and Co-based nanowires. When assembling a two-electrode electrolytic cell with NiCo2 S4 /CC as both the anode and cathode, an applied cell voltage of only 1.66 V is required to deliver a current density of 10 mA cm −2 in water electrolysis. By using the same two-electrode setup, the applied voltage for urea electrolysis is further reduced to 1.45 V that produces hydrogen at the cathode with the same current density. This study paves the way for exploring the feasibility of future less energy-intensive and large-scale hydrogen production.